2020
DOI: 10.1055/s-0040-1713794
|View full text |Cite
|
Sign up to set email alerts
|

Spreader Graft for Severe Deviation of Nasal Septum with Obstruction of the Internal Nasal Valve: Clinical and Functional Results

Abstract: Difficulty in nasal ventilation is one of the most frequently occurring problems in otorhinolaryngology and its correct diagnosis is the key step to solve it. The dysfunctions in the valve area are a frequent cause of chronic nasal obstruction, though commonly ignored. The objective of the study is to analyze the clinical and functional outcomes in a group of patients with septal deviations and valve compromise treated with spreader graft with endonasal approach. Thirty-five patients with septal deviation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Günel et al (56) Lavinsky-Wolff et al (29) 2013 ii −52.0 (−62.9 to −41.1) Sahin et al (66) 2016 −46.4 (−51.4 to −41.3) Shafik et al (67) 2020 −28.5 (−33.0 to −24.0) Yamasaki et al (28) 2019 −39.4 (−41.5 to −37.3) Alan et al (71) 2022 i −55.7 (−67.2 to −44.2)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Günel et al (56) Lavinsky-Wolff et al (29) 2013 ii −52.0 (−62.9 to −41.1) Sahin et al (66) 2016 −46.4 (−51.4 to −41.3) Shafik et al (67) 2020 −28.5 (−33.0 to −24.0) Yamasaki et al (28) 2019 −39.4 (−41.5 to −37.3) Alan et al (71) 2022 i −55.7 (−67.2 to −44.2)…”
Section: Resultsmentioning
confidence: 99%
“…However, 2 randomised trials showed no difference in outcomes after rhinoseptoplasty with and without inferior turbinate treatment with effect sizes on the order of −47/-52 for with/without inferior turbinate reduction (29) and -50/-48 for with/without partial inferior turbinectomy (30) . The minimal differences in the results of our analyses for functional rhinoplasty without concomitant turbinate treatment and all functional rhinoplasty procedures suggest that turbinate treatment may not substantially contribute to the overall treatment effect, which is in alignment with the results of the randomised trials.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation demonstrated that bilateral spreader grafts produce a significantly higher increase of PNIF when compared to spreader flaps, to a combination of spreader flaps plus a unilateral spreader graft or to none of these (Figure 1). Though being expected from their effect on nasal valve widening, the functional role of spreader grafts has not consensus, with some studies demonstrating an improvement of nasal breathing [30][31][32] while other studies could not demonstrate consistent functional benefits. 20,[33][34][35][36] Modifications of spreader grafts have been proposed to improve their functional effect 37,38 and additional techniques, such as the flaring suture 39 or the splay graft 40 have been suggested for the same purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a spreader graft between the septum and the medial surface of the upper lateral cartilage is the standard surgical procedure for the problem of INV stenosis 9 . There are questions that grafts in addition to lateralizing the upper lateral cartilage, they occupy the airway space.…”
Section: Introductionmentioning
confidence: 99%